High-temperature-resistant long-life cable material for charging pile cable and preparation method thereof
Through the use of blending acrylate rubber and ethylene propylene rubber and nanofiller-loaded anti-aging agent, the problem of short service life of charging pile cables in high temperature environments is solved, the thermal oxygen aging resistance and high temperature resistance are improved, and the thermal oxygen aging resistance and high temperature resistance are extended. The service life of cable material.
Patent Information
- Application Number
- CN202411376805.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The service life of charging pile cables in high-temperature environments is short, and the thermal oxygen aging resistance of existing cable materials is insufficient, making it difficult to deal with the high-temperature challenges brought about by the increase in charging time.
Acrylate rubber and ethylene-propylene rubber are blended, and the thermal oxygen aging resistance of cable materials is improved through nanofiller-loaded anti-aging agents, avoiding the migration of anti-aging agents at high temperatures, and forming a multi-dimensional network structure to enhance toughness and temperature resistance.
It significantly improves the high temperature and high temperature service life of cable materials, extends the service life in high temperature environments, enhances the anti-thermal oxidation effect, and can cope with the challenges brought by shortening charging time and increasing current.
Smart Images

Figure BDA0005068884230000051 
Figure BDA0005068884230000111 
Figure BDA0005068884230000121
Abstract
Description
Technical Field
[0001] The present invention relates to the field of cable materials, and in particular to a high-temperature resistant and long-life cable material for charging pile cables and a preparation method thereof. Background Art
[0002] With the rapid development of new energy electric vehicles, the market has put forward higher and higher requirements for charging time. Gradually shortening the charging time to be equivalent to the refueling time of fuel vehicles and improving the user experience are one of the hot spots of future research. At present, the main method to improve the charging time is to increase the charging current. However, a large current during charging will cause the temperature of the charging pile cable to be too high. The cable is at a high temperature for a long time, which will test the performance of the cable material and greatly affect the service life of the cable.
[0003] In order for charging pile cables to cope with the challenges brought by the rapid increase in charging time, the cable materials used need to be resistant to high temperatures and have a long service life. Since the main components of cable materials are mostly polymer materials such as polyolefins, polyurethanes and EPDM rubber, among which EPDM rubber with a higher high temperature resistance can only be used for a short period of time at 150°C. Long-term high temperatures will significantly shorten the service life of the cable. In addition, the ordinary antioxidants added to most cable materials are easily migrated on the surface of the product when heated, which in turn affects its resistance to thermal oxidation aging, greatly reducing the service life of the cable material and limiting its application in charging pile cables. Summary of the invention
[0004] The present invention provides a high-temperature resistant and long-life cable material for charging pile cables and a preparation method thereof, so as to solve the problems of low temperature resistance and short high-temperature service life of current cable material products, improve the thermal oxidation aging resistance of the cable material, and increase the service life in a high-temperature operating environment.
[0005] In order to solve the above technical problems, one of the purposes of the present invention is to provide a high temperature resistant and long life cable material for a charging pile cable, comprising the following components in parts by weight:
[0006] Ethylene propylene rubber: 70-90 parts;
[0007] Acrylic rubber: 10-30 parts;
[0008] Compatibilizer: 5-20 parts;
[0009] Stearic acid: 1-2 parts;
[0010] Zinc oxide: 5-10 parts;
[0011] Paraffin oil: 10-30 parts;
[0012] Vulcanizing agent: 2-5 parts;
[0013] Vulcanizing agent: 1-3 parts;
[0014] Nanofiller-loaded antioxidant: 2-5 parts;
[0015] Reinforcing filler: 20-55 parts.
[0016] By adopting the above scheme, the present application adopts a blend of acrylic rubber and EPDM rubber, which can improve the physical properties of the cable material itself and improve the plasticity of the material. The blended rubber matrix has higher high temperature resistance and improves the temperature resistance grade, which can increase the service life of the cable material in a high temperature operating environment and improve the thermal oxidation resistance effect. Due to the uniform and stable dispersion of the nanomaterial itself in the rubber matrix, the antioxidant is firmly loaded on the nanomaterial, which can not only utilize the nanofiller to improve the reinforcement effect of the cable material, but also avoid the surface migration of the antioxidant at high temperature. The nanomaterial loaded on the antioxidant can further improve the antioxidant's own anti-thermal oxidation aging characteristics, which significantly improves the high temperature resistance and high temperature service life of the cable material as a whole, and can cope with the challenges to the performance of the cable material brought about by the gradual shortening of the charging time of the charging pile and the increasing charging current.
[0017] As a preferred embodiment, the nanomaterial in the nanofiller-loaded antioxidant is loaded on the antioxidant by a silane coupling agent, the nanofiller is at least one of nano white carbon black, nano silicon dioxide, nano carbon black, nano zinc oxide, and nano calcium carbonate, the antioxidant is at least one of 2,2,4-trimethyl-1,2-dihydroquinoline, N-isopropyl-N'-phenyl-p-phenylenediamine, N-(1-methylisopentyl)-N'-phenyl-p-phenylenediamine, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid] pentaerythritol ester, 2-mercaptobenzimidazole, and 4,4-di(phenylisopropyl)diphenylamine, and the silane coupling agent is at least one of γ-aminopropyltriethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, and γ-(methacryloyldeoxy)propyltrimethoxysilane.
[0018] As a preferred embodiment, the preparation method of the nanofiller-supported antioxidant comprises the following steps:
[0019] (1) dispersing the nanofiller in an organic solvent, ultrasonically dispersing to obtain a suspension, then adding a silane coupling agent to the suspension, stirring at 70-90° C. for 3-6 hours, filtering, and washing to obtain a pretreated nanomaterial;
[0020] (2) The pretreated nanofiller and antioxidant are added to an organic solvent, stirred at 70-90° C. for 6-10 hours, washed and dried to obtain the nanofiller loaded antioxidant.
[0021] By adopting the above scheme, the nanofiller is firmly loaded on the surface of the antioxidant through the silane coupling agent, and its binding strength can overcome the force of the high-temperature migration of the antioxidant in the rubber matrix, so that the antioxidant is stably and evenly dispersed in the blended rubber matrix, and synergistically improves the thermal oxidation aging resistance of the cable material with the acrylic rubber, thereby extending the service life.
[0022] As a preferred solution, the particle size of the nanofiller in the nanofiller-loaded antioxidant is 50-70 nm.
[0023] As a preferred embodiment, the EPDM rubber is EPDM, or EPDM in which the third monomer is ethylidene norbornene, ethyl norbornene, dicyclopentadiene, 1,4-hexadiene, or a combination thereof;
[0024] The acrylic rubber is at least one of a chlorine-free polyamine cross-linking type, a self-cross-linking type, a carboxylic acid ammonium salt cross-linking type, and a soap cross-linking type.
[0025] As a preferred embodiment, the compatibilizer is at least one of EPDM rubber grafted with maleic anhydride, EPDM rubber grafted with maleic anhydride, EPDM rubber grafted with silane coupling agent, and EPDM rubber grafted with silane coupling agent.
[0026] By adopting the above scheme, the blended rubber matrix of the present application is mainly composed of EPDM rubber, so EPDM grafted silane coupling agent or maleic anhydride is selected as the preferred compatibilizer, which has a high bonding force with the molecules in the EPDM rubber in the matrix, can promote the cross-linking of EPDM rubber and acrylate rubber to form a multi-dimensional network structure, improve the overall toughness strength and structural stability, and improve the temperature resistance level, thereby extending the service life under high temperature conditions.
[0027] As a preferred embodiment, the vulcanizing agent is at least one of di-tert-butyl peroxyisopropylbenzene, diisopropylbenzene peroxide, hexamethylenediamine carbamate, thiocyanuric acid, trihexamethylenetetramine, and tetrahexamethylenepentamine.
[0028] As a preferred embodiment, the co-vulcanizing agent is at least one of triallyl isocyanurate, N,N-phenylene bismaleimide, divinylbenzene, trialkyl cyanurate, and zinc dibutyl dithiocarbamate (II).
[0029] As a preferred embodiment, the reinforcing filler is at least one of kaolin, talc, calcium carbonate and white carbon black.
[0030] In order to solve the above technical problems, the second object of the present invention is to provide a method for preparing a high temperature resistant and long life cable material for a charging pile cable, comprising the following steps:
[0031] (1) adding acrylate rubber, 10wt%-30wt% paraffin oil, 10wt%-30wt% reinforcing filler, and 10wt%-30wt% nanofiller-loaded antioxidant into a mixing device, mixing and discharging to obtain an acrylate rubber masterbatch;
[0032] (2) adding EPDM rubber, stearic acid, zinc oxide, remaining paraffin oil, remaining white carbon black, and remaining nanofiller-loaded antioxidant into another internal mixing device, and mixing to obtain EPDM rubber masterbatch;
[0033] (3) adding an acrylate rubber masterbatch, an EPDM rubber masterbatch, and a compatibilizer into an internal mixer and blending them together; after blending for 1-3 minutes, adding a vulcanizing agent and a co-vulcanizing agent; and discharging the mixture after blending to obtain an EPDM rubber / acrylate rubber blend;
[0034] (4) The above blended material is put into a granulation device and extruded into granules to obtain a high temperature resistant and long life cable material for charging pile cables.
[0035] As a preferred solution, in step (1), the temperature of the internal mixer is maintained at 40-60° C. and the rotation speed is maintained at 60-100 rpm / min before adding the materials.
[0036] As a preferred solution, in step (2), the temperature of the internal mixer is maintained at 70-90° C. and the rotation speed is maintained at 60-100 rpm / min before adding the materials.
[0037] As a preferred embodiment, in step (3), the mixing temperature is 70-90°C and the rotation speed is 60-100 rpm / min.
[0038] As a preferred embodiment, in step (4), the granulation temperature is 50-60°C, the feeding frequency is 20-30 Hz, the screw frequency is 20-30 Hz, and the pelletizing frequency is 6-8 Hz.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] 1. The present application adopts a blend of acrylic rubber and EPDM rubber, which can improve the physical properties of the cable material and enhance the plasticity of the material. The blended rubber matrix has a higher high temperature resistance, thereby increasing the service life of the cable material in a high temperature operating environment and enhancing the anti-thermal oxidation effect.
[0041] 2. Due to the uniform and stable dispersion of the nanofiller in the rubber matrix, the antioxidant can be firmly loaded on the nanofiller. This can not only utilize the nanofiller to improve the reinforcement effect of the cable material, but also avoid the surface migration of the antioxidant at high temperature, thereby significantly improving the high temperature resistance and high temperature service life of the cable material.
[0042] 3. The blended rubber matrix of the present application is mainly composed of EPDM rubber, and EPDM rubber grafted silane coupling agent or maleic anhydride is selected as the preferred compatibilizer. The bonding force between the molecules of EPDM rubber in the matrix is relatively high, which can promote the cross-linking of EPDM rubber and acrylate rubber to form a multi-dimensional network structure, improve the overall toughness strength and structural stability, and improve the temperature resistance level, thereby extending the service life under high temperature conditions. DETAILED DESCRIPTION
[0043] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Table 1 - Sources of raw materials used in the examples and comparative examples of this application
[0045]
[0046] Preparation Example 1
[0047] A nanofiller-loaded rubber antioxidant, wherein the nanofiller is nanosilicon dioxide, and the loaded antioxidant is 2-mercaptobenzimidazole, and the preparation method thereof comprises the following preparation steps:
[0048] (1) 20 g of nano-silicon dioxide (particle size of 60 nm) was dispersed in 550 ml of anhydrous ethanol, and ultrasonically dispersed at room temperature for 15 min to obtain a suspension, and then 4 g of silane coupling agent A-174 was added to the suspension, stirred at 80° C. for 5 h, filtered, and washed with anhydrous ethanol to obtain pretreated nano-silicon dioxide;
[0049] (2) 10 g of pretreated nano-silica and 2 g of 2-mercaptobenzimidazole were added to 300 ml of anhydrous ethanol solution and stirred at 80° C. for 8 h. The obtained product was washed with anhydrous ethanol and placed in a vacuum oven and dried at 60° C. for 24 h to obtain nano-silica loaded with 2-mercaptobenzimidazole.
[0050] Preparation Example 2
[0051] A nano-filler loaded rubber antioxidant, wherein the nano-filler is nano-silicon dioxide and the loaded antioxidant is 2-mercaptobenzimidazole, comprises the following preparation steps:
[0052] (1) dispersing 20 g of nano-silica in 550 ml of anhydrous ethanol, ultrasonically dispersing for 15 min at room temperature to obtain a suspension, then adding 4 g of silane coupling agent A-174 to the suspension, stirring at 80° C. for 5 h, filtering, and washing with anhydrous ethanol to obtain pretreated nano-silica;
[0053] (2) 10 g of pretreated nano-silica and 2 g of 2,2,4-trimethyl-1,2-dihydroquinoline were added to 300 ml of anhydrous ethanol solution and stirred at 80° C. for 8 h. The obtained product was washed with anhydrous ethanol and placed in a vacuum oven and dried at 60° C. for 24 h to obtain nano-silica-loaded 2,2,4-trimethyl-1,2-dihydroquinoline.
[0054] Preparation Example 3
[0055] An EPDM rubber grafted silane coupling agent, the preparation method of which comprises the following steps:
[0056] 100g of EPDM rubber, 8g of KH550 silane coupling agent, and 1g of dicumyl peroxide were added to an open mill, pre-milled at 45°C for 7min, and then put into a Haake torque rheometer with the rotor speed set at 70rpm / min and heat-milled at 180°C for 5min to obtain EPDM rubber grafted silane coupling agent (EPDM-gS).
[0057] Example 1
[0058] A high temperature resistant and long life cable material for a charging pile cable comprises acrylate rubber, ethylene propylene diene monomer rubber, paraffin oil, white carbon black, nano-silica loaded with 2-mercaptobenzimidazole of Preparation Example 1, nano-silica loaded with 2,2,4-trimethyl-1,2-dihydroquinoline of Preparation Example 2, stearic acid, zinc oxide, ethylene propylene diene monomer rubber grafted silane coupling agent of Preparation Example 3, diisopropylbenzene peroxide, trithiocyanic acid, triallyl isocyanurate and zinc dibutyl dithiocarbamate (II), the particle size of the white carbon black is 50 nm, the particle size of the zinc oxide is 60 nm, and the preparation method comprises the following steps:
[0059] (1) The temperature of the internal mixer was set to 50° C. and the speed was set to 80 rpm / min. After the temperature was stabilized, 10 kg of acrylic rubber, 2 kg of paraffin oil, 5 kg of carbon black, 0.375 kg of nano-silica-loaded 2-mercaptobenzimidazole and 0.125 kg of nano-silica-loaded 2,2,4-trimethyl-1,2-dihydroquinoline were added, and the mixture was mixed for 3 minutes and then discharged to obtain an acrylic rubber masterbatch;
[0060] (2) raising the temperature of the internal mixer to 80° C. and the speed to 80 rpm / min. After the temperature stabilizes, adding 90 kg of EPDM rubber, 1 kg of stearic acid, 5 kg of zinc oxide, 18 kg of paraffin oil, 45 kg of white carbon black, 3.375 kg of nano-silica-loaded 2-mercaptobenzimidazole and 1.125 kg of nano-silica-loaded 2,2,4-trimethyl-1,2-dihydroquinoline, and mixing for 5 minutes to obtain an EPDM rubber masterbatch;
[0061] (3) adding all the above-mentioned acrylic rubber masterbatch, EPDM rubber masterbatch, and 5 kg of EPDM rubber grafted silane coupling agent into an internal mixer and blending them at a mixing temperature of 80° C. and a rotation speed of 80 rpm / min. After blending for 2 min, 3.6 kg of diisopropylbenzene peroxide, 0.4 kg of trithiocyanuric acid, 1 kg of triallyl isocyanurate, and 0.5 kg of zinc dibutyl dithiocarbamate (II) were added. After blending for 3 min, the mixture was discharged to obtain an EPDM rubber / acrylate rubber blend;
[0062] (4) The above blended material is put into a granulator with a granulation temperature of 60° C., a feeding frequency of 25 Hz, a screw frequency of 25 Hz, and a pelletizing frequency of 7 Hz. After being extruded into granules, a high-temperature resistant and long-life cable material for charging pile cables is obtained.
[0063] Example 2
[0064] A high temperature resistant and long life cable material for a charging pile cable comprises acrylate rubber, ethylene propylene diene monomer rubber, paraffin oil, white carbon black, nano-silica loaded with 2-mercaptobenzimidazole of Preparation Example 1, nano-silica loaded with 2,2,4-trimethyl-1,2-dihydroquinoline of Preparation Example 2, stearic acid, zinc oxide, ethylene propylene diene monomer rubber grafted silane coupling agent of Preparation Example 3, diisopropylbenzene peroxide, trithiocyanic acid, triallyl isocyanurate and zinc dibutyl dithiocarbamate (II), the particle size of the white carbon black is 50 nm, the particle size of the zinc oxide is 60 nm, and the preparation method comprises the following steps:
[0065] (1) The temperature of the internal mixer was set to 50° C. and the speed was set to 80 rpm / min. After the temperature was stabilized, 20 kg of acrylic rubber, 4 kg of paraffin oil, 10 kg of carbon black, 0.75 kg of nano-silica-loaded 2-mercaptobenzimidazole and 0.25 kg of nano-silica-loaded 2,2,4-trimethyl-1,2-dihydroquinoline were added, and the mixture was mixed for 3 minutes and then discharged to obtain an acrylic rubber masterbatch;
[0066] (2) raising the temperature of the internal mixer to 80° C. and the speed to 80 rpm / min. After the temperature stabilizes, adding 80 kg of EPDM rubber, 1 kg of stearic acid, 5 kg of zinc oxide, 16 kg of paraffin oil, 40 kg of white carbon black, 3 kg of nano-silica-loaded 2-mercaptobenzimidazole and 1 kg of nano-silica-loaded 2,2,4-trimethyl-1,2-dihydroquinoline, and mixing for 5 minutes to obtain an EPDM rubber masterbatch;
[0067] (3) adding all the above-mentioned acrylic rubber masterbatch, EPDM rubber masterbatch, and 10 kg of EPDM rubber grafted silane coupling agent into an internal mixer and blending them at a mixing temperature of 80° C. and a rotation speed of 80 rpm / min. After blending for 2 min, 3.2 kg of diisopropylbenzene peroxide, 0.8 kg of trithiocyanuric acid, 1 kg of triallyl isocyanurate, and 0.5 kg of zinc dibutyl dithiocarbamate (II) were added. After blending for 3 min, the mixture was discharged to obtain an EPDM rubber / acrylate rubber blend;
[0068] (4) The above blended material is put into a granulator with a granulation temperature of 60° C., a feeding frequency of 25 Hz, a screw frequency of 25 Hz, and a pelletizing frequency of 7 Hz. After being extruded into granules, a high-temperature resistant and long-life cable material for charging pile cables is obtained.
[0069] Example 3
[0070] A high temperature resistant and long life cable material for a charging pile cable comprises acrylate rubber, ethylene propylene diene monomer rubber, paraffin oil, white carbon black, nano-silica loaded with 2-mercaptobenzimidazole of Preparation Example 1, nano-silica loaded with 2,2,4-trimethyl-1,2-dihydroquinoline of Preparation Example 2, stearic acid, zinc oxide, ethylene propylene diene monomer rubber grafted silane coupling agent of Preparation Example 3, diisopropylbenzene peroxide, trithiocyanic acid, triallyl isocyanurate and zinc dibutyl dithiocarbamate (II), the particle size of the white carbon black is 50 nm, the particle size of the zinc oxide is 60 nm, and the preparation method comprises the following steps:
[0071] (1) The temperature of the internal mixer was set to 50° C. and the speed was set to 80 rpm / min. After the temperature was stabilized, 25 kg of acrylic rubber, 6 kg of paraffin oil, 15 kg of carbon black, 1.125 kg of nano-silica-loaded 2-mercaptobenzimidazole and 0.375 kg of nano-silica-loaded 2,2,4-trimethyl-1,2-dihydroquinoline were added, and the mixture was mixed for 3 minutes and then discharged to obtain an acrylic rubber masterbatch;
[0072] (2) The temperature of the internal mixer was raised to 80° C. and the speed was 80 rpm / min. After the temperature stabilized, 75 kg of EPDM rubber, 1 kg of stearic acid, 5 kg of zinc oxide, 14 kg of paraffin oil, 35 kg of white carbon black, 2.625 kg of nano-silica-loaded 2-mercaptobenzimidazole and 0.875 kg of nano-silica-loaded 2,2,4-trimethyl-1,2-dihydroquinoline were added, and mixed for 5 minutes to obtain an EPDM rubber masterbatch;
[0073] (3) adding all the above-mentioned acrylic rubber masterbatch, EPDM rubber masterbatch, and 15 kg of EPDM rubber grafted silane coupling agent into an internal mixer and blending them at a mixing temperature of 80° C. and a rotation speed of 80 rpm / min. After blending for 2 min, 3 kg of diisopropylbenzene peroxide, 1 kg of trithiocyanic acid, 1 kg of triallyl isocyanurate, and 0.5 kg of zinc dibutyl dithiocarbamate (II) were added. After blending for 3 min, the mixture was discharged to obtain an EPDM rubber / acrylate rubber blend;
[0074] (4) The above blended material is put into a granulator with a granulation temperature of 60° C., a feeding frequency of 25 Hz, a screw frequency of 25 Hz, and a pelletizing frequency of 7 Hz. After being extruded into granules, a high-temperature resistant and long-life cable material for charging pile cables is obtained.
[0075] Example 4
[0076] A high-temperature resistant and long-life cable material for a charging pile cable, wherein the steps of the preparation method thereof, the reagents used in the steps, and the process parameters are the same as those in Example 3, except that the nano-silica-loaded 2-mercaptobenzimidazole of Preparation Example 1 is replaced by an equal amount of the nano-silica-loaded 2,2,4-trimethyl-1,2-dihydroquinoline of Preparation Example 2.
[0077] Example 5
[0078] A high-temperature resistant and long-life cable material for charging pile cables, wherein the steps of the preparation method thereof, the reagents used in the steps, and the process parameters are the same as those in Example 3, except that the EPDM rubber grafted silane coupling agent in Preparation Example 3 is replaced by an equal amount of maleic anhydride grafted EPDM rubber.
[0079] Comparative Example 1
[0080] A cable material for a charging pile cable comprises ethylene propylene diene monomer rubber, paraffin oil, white carbon black, nano-silica loaded with 2-mercaptobenzimidazole of Preparation Example 1, nano-silica loaded with 2,2,4-trimethyl-1,2-dihydroquinoline of Preparation Example 2, stearic acid, zinc oxide, ethylene propylene diene monomer rubber grafted with silane coupling agent of Preparation Example 3, diisopropylbenzene peroxide, trithiocyanic acid, triallyl isocyanurate and zinc dibutyl dithiocarbamate (II), the particle size of the white carbon black is 50 nm, the particle size of the zinc oxide is 60 nm, and the preparation method comprises the following steps:
[0081] (1) The temperature of the internal mixer was raised to 80° C. and the speed was 80 rpm / min. After the temperature was stabilized, 100 kg of EPDM rubber, 1 kg of stearic acid, 5 kg of zinc oxide, 20 kg of paraffin oil, 50 kg of white carbon black, 3.75 kg of nano-silica-loaded 2-mercaptobenzimidazole and 1.25 kg of nano-silica-loaded 2,2,4-trimethyl-1,2-dihydroquinoline were added, and mixed for 5 minutes to obtain an EPDM rubber masterbatch;
[0082] (2) adding all the above EPDM masterbatch and 15 kg of EPDM grafted silane coupling agent into an internal mixer for blending at a mixing temperature of 80° C. and a rotation speed of 80 rpm / min. After blending for 2 min, adding 3 kg of diisopropylbenzene peroxide, 1 kg of trithiocyanic acid, 1 kg of triallyl isocyanurate, and 0.5 kg of zinc dibutyl dithiocarbamate (II), blending for 3 min, and then discharging the mixture to obtain an EPDM blend;
[0083] (3) The above blended material is put into a granulator with a granulation temperature of 60° C., a feeding frequency of 25 Hz, a screw frequency of 25 Hz, and a pelletizing frequency of 7 Hz. After being extruded into granules, a cable material for a charging pile cable is obtained.
[0084] Comparative Example 2
[0085] A high-temperature resistant and long-life cable material for a charging pile cable, wherein the steps of the preparation method thereof, the reagents used in the steps, and the process parameters are the same as those in Example 3, except that the nano-silica-loaded 2-mercaptobenzimidazole in Preparation Example 1 is replaced by an equal amount of 2-mercaptobenzimidazole, and the nano-silica-loaded 2,2,4-trimethyl-1,2-dihydroquinoline in Preparation Example 2 is replaced by an equal amount of 2,2,4-trimethyl-1,2-dihydroquinoline.
[0086] Comparative Example 3
[0087] A high-temperature resistant and long-life cable material for a charging pile cable, wherein each step of the preparation method and the reagents and process parameters used in each step are the same as those in Example 3, except that the amount of paraffin oil added is 0.
[0088] Comparative Example 4
[0089] A high-temperature resistant and long-life cable material for charging pile cables, wherein each step of the preparation method and the reagents and process parameters used in each step are the same as those in Example 3, except that the amount of ethylene propylene diene rubber grafted silane coupling agent added in Preparation Example 3 is 0.
[0090] Performance testing
[0091] 1. According to GB / T 528-2009 standard, the tensile strength and elongation at break of cable material samples prepared in the embodiment and the comparative example were tested. The test samples were hot-pressed at 180° C. for 10 min using a flat vulcanizer. The sample size was 5 cm×5 cm×1 cm. The test results are shown in Table 2 below.
[0092] 2. The insulation resistance constant of the cable material samples prepared in the embodiment and the comparative example was measured according to GB / T 33594-2017 standard. The sample size was 5 cm×5 cm×1 cm. The test sample was hot pressed at 180°C for 10 min using a flat vulcanizer. The test temperature was 20°C. The test results are shown in Table 2 below.
[0093] 3. The cable material samples prepared in the examples and comparative examples were subjected to a thermal oxidation aging test in accordance with GB / T 2951.12-2008. The test samples were prepared by hot pressing at 180°C for 10 minutes using a flat vulcanizer. The tensile strength change rate and elongation at break change rate of the cable material were tested at 165°C for 168 hours. The test results are shown in Table 2 below.
[0094] 4. According to GB / T 2951.21-2008 standard, the cable material samples prepared in the embodiments and comparative examples were subjected to a hot extension test. The test samples were prepared by hot pressing at 180°C for 10 min using a flat vulcanizer. The sample size was 5 cm×5 cm×1 cm. The test temperature was 250°C for 15 min. The maximum elongation under the test load and the permanent elongation after cooling were measured. The test results are shown in Table 2 below.
[0095] 5. According to GB / T 2951.21-2008 standard, the cable material samples prepared in the embodiment and the comparative example were subjected to ozone resistance test. The test samples were prepared by hot pressing at 180°C for 10 minutes using a flat vulcanizer. The sample size was 5 cm×5 cm×1 cm. The experimental conditions were ozone concentration of 0.03%, temperature of 25°C, and time of 24 hours. The samples were observed to see if they cracked. The test results are shown in Table 2 below.
[0096] Table 2 - Performance test results of cable material products prepared in the examples and comparative examples of the present application
[0097]
[0098]
[0099] By comparing the performance test results of Example 3 and Comparative Examples 1-2 in Table 2, it can be seen that the present application blends acrylate rubber and EPDM rubber to improve the overall high temperature resistance, and utilizes EPDM rubber grafted silane coupling agent to promote the compatibility of acrylate rubber and EPDM rubber matrix, improve the physical properties of the cable material itself, and has high plasticity. The high temperature resistance of the cable material is significantly improved. At the same time, due to the properties of the nanomaterial itself, the nanomaterial-loaded antioxidant has high stability in the cable material, is not easy to migrate to the surface of the material, is more evenly dispersed, and can even act as a reinforcing agent, which can avoid excessive local aging of the material and balance the heat-oxidative aging resistance. After running at a temperature of 165°C for 168 hours, the tensile strength is only increased by about 19%, and the elongation is only reduced by about 16%. Compared with Comparative Examples 1-2, the heat-oxidative aging resistance of Example 3 is improved, and the service life is longer.
[0100] By comparing the performance test results of Examples 3 and 5 and Comparative Example 4 in Table 2, it can be seen that compared with Comparative Example 4, Example 6 adds maleic anhydride grafted EPDM rubber, and the prepared cable material has higher plasticity and high temperature aging resistance. Compared with Example 5, the EPDM grafted maleic anhydride added in Example 3 of the present application can effectively promote the compatibility of acrylic rubber and EPDM rubber matrix by grafting more EPDM rubber, and has high temperature aging resistance while further improving the plasticity of the cable material.
[0101] By comparing the performance test results of Example 3 and Comparative Examples 2-3 in Table 2, it can be seen that the antioxidants in Comparative Example 2 are 2-mercaptobenzimidazole and 2,2,4-trimethyl-1,2-dihydroquinoline, while Comparative Example 3 does not add paraffin oil. The finally obtained cable material has low resistance to thermal oxidative aging. In a hot oxidative environment, the cable material undergoes oxidation hardening, resulting in increased hardness and reduced plasticity. Example 3 of the present application can not only improve the original toughness of the cable material, but also improve the thermal oxidative aging resistance of the cable material by adding nanomaterial-loaded antioxidants and paraffin oil at the same time, thereby meeting application requirements.
[0102] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. It is particularly pointed out that for those skilled in the art, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of protection of the present invention.
Claims
1. A high temperature resistant and long life cable material for charging pile cables, characterized in that: The composition comprises the following components in parts by weight: Ethylene propylene rubber: 70-90 parts; Acrylic rubber: 10-30 parts; Compatibilizer: 5-20 parts; Stearic acid: 1-2 parts; Zinc oxide: 5-10 parts; Paraffin oil: 10-30 parts; Vulcanizing agent: 2-5 parts; Vulcanizing agent: 1-3 parts; Nanofiller-loaded antioxidant: 2-5 parts; Reinforcing filler: 20-55 parts.
2. The high temperature resistant and long life cable material for charging pile cables according to claim 1, characterized in that: The nanofiller in the nanofiller-loaded antioxidant is loaded on the antioxidant by a silane coupling agent, the nanofiller is at least one of nano white carbon black, nano silicon dioxide, nano carbon black, nano zinc oxide, and nano calcium carbonate, the antioxidant is at least one of 2,2,4-trimethyl-1,2-dihydroquinoline, N-isopropyl-N'-phenyl-p-phenylenediamine, N-(1-methylisopentyl)-N'-phenyl-p-phenylenediamine, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid] pentaerythritol ester, 2-mercaptobenzimidazole, and 4,4-di(phenylisopropyl)diphenylamine, and the silane coupling agent is at least one of γ-aminopropyltriethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, and γ-(methacryloyldeoxy)propyltrimethoxysilane.
3. A high temperature resistant and long life cable material for charging pile cables as claimed in claim 2, characterized in that: The preparation method of the nanofiller-supported antioxidant comprises the following steps: (1) dispersing the nanofiller in an organic solvent, ultrasonically dispersing to obtain a suspension, then adding a silane coupling agent to the suspension, stirring at 70-90° C. for 3-6 hours, filtering, and washing to obtain a pretreated nanomaterial; (2) The pretreated nanofiller and antioxidant are added to an organic solvent, stirred at 70-90° C. for 6-10 hours, washed and dried to obtain the nanofiller loaded antioxidant.
4. The high temperature resistant and long life cable material for charging pile cables according to claim 1, characterized in that: The EPDM rubber is EPDM, or EPDM in which the third monomer is ethylidene norbornene, ethyl norbornene, dicyclopentadiene, 1,4-hexadiene, or a combination thereof; The acrylic rubber is at least one of a chlorine-free polyamine cross-linking type, a self-cross-linking type, a carboxylic acid ammonium salt cross-linking type, and a soap cross-linking type.
5. The high temperature resistant and long life cable material for charging pile cables according to claim 1, characterized in that: The compatibilizer is at least one of EPDM rubber grafted with maleic anhydride, EPDM rubber grafted with maleic anhydride, EPDM rubber grafted with silane coupling agent, and EPDM rubber grafted with silane coupling agent.
6. The high temperature resistant and long life cable material for charging pile cables according to claim 1, characterized in that: The vulcanizing agent is at least one of di-tert-butyl peroxyisopropylbenzene, diisopropylbenzene peroxide, hexamethylenediamine carbamate, thiocyanuric acid, trihexamethylenetetramine and tetrahexamethylenepentamine.
7. The high temperature resistant and long life cable material for charging pile cables according to claim 1, characterized in that: The co-vulcanizing agent is at least one of triallyl isocyanurate, N,N-phenylene bismaleimide, divinylbenzene, trialkyl cyanurate, and zinc dibutyl dithiocarbamate (II).
8. The high temperature resistant and long life cable material for charging pile cables according to claim 1, characterized in that: The reinforcing filler is at least one of kaolin, talc, calcium carbonate and white carbon black.
9. A method for preparing a high temperature resistant and long life cable material for a charging pile cable according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) adding acrylate rubber, 10wt%-30wt% paraffin oil, 10wt%-30wt% reinforcing filler, and 10wt%-30wt% nanofiller-loaded antioxidant into a mixing device, mixing and discharging to obtain an acrylate rubber masterbatch; (2) adding EPDM rubber, stearic acid, zinc oxide, remaining paraffin oil, remaining white carbon black, and remaining nanofiller-loaded antioxidant into another internal mixing device, and mixing to obtain EPDM rubber masterbatch; (3) adding an acrylate rubber masterbatch, an EPDM rubber masterbatch, and a compatibilizer into an internal mixer and blending them together; after blending for 1-3 minutes, adding a vulcanizing agent and a co-vulcanizing agent; and discharging the mixture after blending to obtain an EPDM rubber / acrylate rubber blend; (4) The above blended material is put into a granulation device and extruded into granules to obtain a high temperature resistant and long life cable material for charging pile cables.
10. The method for preparing a high temperature resistant and long life cable material for a charging pile cable according to claim 9, characterized in that: Satisfy at least one of the following a)-d): a) In step (1), the temperature of the internal mixer is maintained at 40-60° C. and the rotation speed is maintained at 60-100 rpm / min before adding the materials; b) in step (2), the temperature of the internal mixer is maintained at 70-90° C. and the speed is maintained at 60-100 rpm / min before adding the materials; c) in step (3), the mixing temperature is 70-90° C. and the rotation speed is 60-100 rpm / min; d) In step (4), the granulation temperature is 50-60°C, the feeding frequency is 20-30 Hz, the screw frequency is 20-30 Hz, and the pelletizing frequency is 6-8 Hz.
Citation Information
Patent Citations
Heat resistant and oil resistant ethylene propylene diene monomer rubber / acrylate rubber cable material
CN105111592A
Preparation method ethylene-propylene rubber cable insulation material
CN106188887A
Heat-conducting insulating ethylene propylene rubber composite material as well as preparation method and application thereof
CN116675931A
Rubber composite, processing method, rubber products applying composite, and manufacturing method
WO2018130194A1
Cited By
Waterproof corrosion-resistant cable material, preparation method thereof and cable
CN121628261A
A waterproof and corrosion-resistant cable material and a preparation method thereof, and a cable
CN121628261B
